Sejarah Perkembangan Islam di Indonesia Era Reformasi - M Dahlan M (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2011)
This writing explores the sense history of Islam as religion most adhered by people of Indonesia. The approach used in this writing is history. This article concluded that Islam has reached Indonesia at 13 century and increasly spread at 17 century. It is due to the support of some Kings who ruled some regions in Indonesia. When reformation era came, Islam get more progress supported by the exixtence of Islamic organization. Furthermore, Islam now is noted to have 88% adherents in Indonesia. It is due to the roles of Islamic preaching in Indonesia.